(untitled) (Journal of Engineering, 2022)
Soils that cause effective damages to engineer structures (such as pavement and foundation) are called problematic or difficult soils (include collapsible soil, expansive soil, etc.). These damages occur due to poor or unfavorited engineering properties, such as low shear strength, high compressibility, high volume changes, etc. In the case of expansive soil, the problem of the shrink-swell phenomenon, when the soil reacts with water, is more pronounced. To overcome such problems, soils can be treated or stabilized with many stabilization ways (mechanical, chemical, etc.). Such ways can amend the unfavorited soil properties. In this review, the pozzolanic materials have been selected to be presented and discussed as chemical stabilizers. The selected pozzolanic materials are traditional, industrial, or byproducts, ashes of agricultural wastes, and calcined-clay types. They are lime, cement, blast furnace slag, fly ash, silica fume, rice husk ash, sugarcane straw ash, egg ash, coconut husk ash, and metakaolin. In general, the stabilization of expansive soils with pozzolanic materials has an essential impact on swelling and Atterberg-limits and positively affects compaction and strength parameters. However, there is a wide range for the percentages of pozzolanic materials used as stabilizers. The content (15% to 20%) is the most ratios of the stabilizers used as an optimal percentage, and beyond this ratio, the addition of the pozzolanic materials produces an undesirable effect.